LEADERSHIP STYLE IN GARMENT COMPANIES IN WEST JAVA, AND THEIR EFFECT ON JOB SATISFACTION - Ammirudin, Ammirudin; Moeins, Anoesyirwan (Dinasti International Journal of Management Science, 2021)
Indonesia is one of the developing countries that will enter the era of globalization so that competition will be tougher, especially in the industrial sector. Rapid changes in science and technology will lead to increasingly complex problems and activities faced by company leaders. The desires of organizational members need to be combined with the planned company goals so that there is an integrated movement in achieving company goals. Leaders are required to have the knowledge, understanding, and skills to lead the field of work wherever he is and how the conditions are. So the position of the leader is a determining factor in achieving goals, even though there has been a neatly arranged plan, but if there is no one who makes organizational management attractive to all personnel